Efficacy and mechanism of long-snake moxibustion for treating insomnia in breast cancer survivors: study protocol for a randomized controlled trial - Gong, Cuicui; Li, Huakang; Li, Qiang; Gu, Pengxuan; Xiao, Qi; Jia, Yunjing; Xiao, Qian; Mi, Yuanzhen; Wei, Shanshan; Wu, Ziliang; Lin, Bing; Zhang, Zhonglin (Frontiers in Neurology, 2025)
BackgroundInsomnia (difficulty falling or staying asleep) is a common issue among breast cancer survivors, significantly impacting their quality of life. Current treatments, primarily pharmacological and psychological, have limitations: the former often causes side effects, while the latter faces accessibility barriers. Long-snake moxibustion (LSM), a traditional Chinese medicine (TCM) technique, involves applying moxibustion along the governor vessel, which is an important meridian in TCM that plays a key role in regulating brain function. LSM is characterized by its minimal side effects, ease of application, and cost-effectiveness, with preliminary studies supporting its potential for treating insomnia. This study aims to further investigate the therapeutic effectiveness of LSM in alleviating insomnia among breast cancer survivors and to explore its underlying mechanisms.MethodsThis single-center, rater-masked, randomized controlled trial will enroll 100 breast cancer survivors with chronic insomnia, who will be randomly assigned in a 1:1 ratio to either the LSM group or a waitlist control group. During the 4-week treatment period, all participants will receive standard care, with the LSM group additionally receiving LSM treatment twice a week. The primary efficacy outcome is the change in Insomnia Severity Index (ISI) score at the end of the intervention. Secondary outcomes include changes in hypnotic medication use, Pittsburgh Sleep Quality Index (PSQI) scores, Piper Fatigue Scale (PFS) scores, and Functional Assessment of Cancer Therapy-Breast (FACT-B) scores. Mechanistic evaluations will assess serum biochemical markers, gut microbiota composition, and metabolomic profiles.DiscussionIf proven effective, this trial will provide critical clinical evidence supporting LSM as a viable and accessible treatment for insomnia among breast cancer survivors. The findings could influence clinical practice by offering a non-pharmacological treatment option, improving patient outcomes, and reducing dependence on pharmacological interventions. Furthermore, exploring the underlying mechanisms may enhance our understanding of how LSM works, paving the way for future research.Clinical trial registrationhttp://itmctr.ccebtcm.org.cn/, identifier ITMCTR2024000578.